2001
DOI: 10.1080/106689201753235903
|View full text |Cite
|
Sign up to set email alerts
|

Dropout and Stopout Patterns Among Developmental Education Students in Texas Community Colleges

Abstract: The dropout/stopout patterns of community college students were examined in the research reported here. About two thirds of the 51,903 students in the study were enrolled in developmental education courses. Success in college was deüned as a passing grade point average after üve semesters of coursework . Student success was found to be associated with enrollment patterns, initial skill deüciencies, and age. Community college students who enrolled for consecutive semesters outperformed students with other types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Approximately 25% to 45% of incoming college freshmen never graduate (Solberg Nes, Evans, & Segerstrom, 2009). Researchers have shown that the rate of successful remediation in postsecondary institutions is very low (e.g., Adelman, 2005;Bahr, 2010;Burley, Butner, & Cejda, 2001). More than 25% of students who must take three or more remedial classes drop out of college after the first year (Adelman, 2005).…”
Section: Failure To Persist To Graduation From Collegementioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 25% to 45% of incoming college freshmen never graduate (Solberg Nes, Evans, & Segerstrom, 2009). Researchers have shown that the rate of successful remediation in postsecondary institutions is very low (e.g., Adelman, 2005;Bahr, 2010;Burley, Butner, & Cejda, 2001). More than 25% of students who must take three or more remedial classes drop out of college after the first year (Adelman, 2005).…”
Section: Failure To Persist To Graduation From Collegementioning
confidence: 99%
“…More than 25% of students who must take three or more remedial classes drop out of college after the first year (Adelman, 2005). The more remedial classes students must take during their first years of college, the more likely it is that they will drop out (Burley et al, 2001). Moreover, of those students who do not drop out during their 1st year of college, those who must take a remedial mathematics course typically do not develop the level of mathematics skill that would allow them to graduate or that could make them competitive for higher demand jobs.…”
Section: Failure To Persist To Graduation From Collegementioning
confidence: 99%
“…A number of published studies have reported that post-secondary educational programs suffer from a high rate of student attrition-in both traditional face-to-face instruction and distance education programs. For example, Burley, Butner, and Cejda (2001) reported that approximately 50% of students who enter undergraduate degree programs actually complete those programs. A similar result was reported by Desjardins, Ahlburg, and McCall (2002).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…As a result, a great deal of research has been carried out to identify the factors that contribute to drop-out and to investigate ways to reduce it. One of the major challenges associated with this area of research has been the recognition that drop-out behaviour in post-secondary studies is a complex phenomenon that typically results from multiple causes (see Bonham & Luckie, 1993a;Burley et al, 2001;Desjardins et al, 2002;Summers, 2003). Woodley (2004) observed that two general approaches have characterized research into the phenomenon of drop-out.…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 1 more Smart Citation